DESIGN OF TESTING DEVICE FOR ASSESSMENT OF BOND BETWEEN PAVEMENT LAYERS ON MALAYSIAN ROAD CONSTRUCTION - Ahmad Pauzi, Ahmad Haziq Fitri (Universiti Teknologi PETRONAS, 2018)
Road pavement usually composed of several layers of different materials and most of pavement design and evaluation methods assume that those layers are fully bonded together as a composite structure. A thin layer of bitumen tack coat is usually applied at the interface to ensure a proper bonding which is not always achieved. Several projects have been conducted throughout the world to study the effect of bond condition on pavement performance. The research show that the interlayer bond significantly influences the distribution of stress, strain and deflection within the pavement structure (Romain, 1968; Uzan et al., 1978; Brown and Brunton, 1984; Shahin et al., 1987; Al Hakim, 1997; Hachiya and Sato, 1997; Kruntcheva et al., 2000; Sutanto, 2010).